Technology and Culture-Based Career Guidance Strategies in Secondary Schools - Agus Setiawan; Palasara Brahmani Laras; Adi Atmoko; Arbin Janu Setyowati; Punaji Setyosari; Nur Eva (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study examines the implementation of career guidance and counseling in high schools using a Systematic Literature Review (SLR) approach. The authors reviewed 26 papers that met the exclusion criteria related to career guidance. Among these, 10 papers were selected based on inclusion criteria relevant to career guidance and counseling in secondary schools during the period 2014-2024. This study aims to identify trends, approaches, and interventions that effectively prepare students for career challenges. The results show that integrating digital technology, culture-based approaches, and hands-on field experience is the primary strategy for improving students' career readiness. However, challenges such as limited resources, gaps in access to technology, and a lack of training for supervisors remain obstacles to implementation. Therefore, cross-sector collaboration is considered essential to create a career guidance system that is adaptive, inclusive, and responsive to global demands. Keywords: career guidance, high school, systematic literature review, digital technology, local culture